Re-use of public sector information in cultural heritage institutions (Journal of Open Law, Technology & Society, 2014)
In 2013 the European Union amended the Directive on Public Sector Information, establishing the principle that all available information produced and collected by public sector institutions must be made available for reuse under open terms and conditions. The amended Directive also brings publicly funded libraries, museums and archives into its scope. These new rules on reuse of heritage materials, treated as public sector information (PSI), attempt for the first time to define a general framework for sharing cultural heritage information all around Europe. In this paper we argue that if Member States are not careful, the implementation of the changes required by the new Directive could do more harm than good when it comes to access to digitized cultural heritage in Europe. These concerns center on how the directive interacts with copyright legislation. The paper recommends that in order to contribute to the opening up of cultural heritage resources, Member States should ensure that all qualifying documents that are not currently covered by third party intellectual property rights fall within the scope of the Directive. Member States should also implement the Directive in a way that does not encourage or require institutions to charge for the reuse of works that they make available for reuse. For documents that are still protected by intellectual property rights but where these rights are held by the cultural heritage institutions that have these works in their collections, Member States should encourage the use of Open Definition-compliant licenses.